2006
DOI: 10.1038/sj.sc.3101907
|View full text |Cite
|
Sign up to set email alerts
|

Micturition syncope following intermittent catheterisation in a tetraplegic patient

Abstract: Study design: Case report. Objective: To describe a case of severe hypotension and occasional syncope following intermittent catheterisations in a tetraplegic patient. Setting: Department of Spinal Injuries, Berck, France. Case report: A 47-year-old man presenting with C7 ASIA B tetraplegia for 9 months, developed episodes of severe hypotension and occasional syncope following intermittent catheterisations. These episodes were observed in the minutes following the catheterisations performed in the sitting posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Micturition syncope can be an isolated symptom in healthy subjects, but it is frequently associated with other neurological causes, such as autonomic failure of primary (multiple system atrophy; MSA) or secondary (such as diabetes) etiology. In addition, it was reported that intermittent catheterization caused micturition syncope in a quadriplegic patient due to cervical spinal cord injury that was accompanied with autonomic dysreflexia [2,10]. …”
Section: Discussionmentioning
confidence: 99%
“…Micturition syncope can be an isolated symptom in healthy subjects, but it is frequently associated with other neurological causes, such as autonomic failure of primary (multiple system atrophy; MSA) or secondary (such as diabetes) etiology. In addition, it was reported that intermittent catheterization caused micturition syncope in a quadriplegic patient due to cervical spinal cord injury that was accompanied with autonomic dysreflexia [2,10]. …”
Section: Discussionmentioning
confidence: 99%
“…Micturition syncope can be caused by the vasovagal reflex or with the dysfunction of the blood pressure regulating mechanism (as in hypotension), which occurs before, during, or immediately after urination. It has been reported especially in male patients, associated with orthostatism, in healthy people, especially in the age group of 40 to 50 years, or in those with neurological disorders, [ 1 , 2 ] diabetes mellitus, spinal cord injuries, [ 3 ] patients that are on vasodilator medication or depression medication (selective serotonin reuptake inhibitors and tricyclic antidepressants), antipsychotics and levodopa.…”
Section: Introductionmentioning
confidence: 99%
“…As described in the literature, neoplastic diseases such as a paraganglioma of the urinary bladder [ 4 ] or intermittent urinary bladder catheterization in patients with neurological disorders can be associated with micturition syncope. [ 3 ] The occurrence of micturition syncope in the clinical course of SARS-CoV-2 infection in the 4 patients of different ages, with or without comorbidities, raises the issue of the association of micturition syncope with coronavirus infection.…”
Section: Introductionmentioning
confidence: 99%